Long-term observation of the in vivo safety of a new design of phakic refractive lens - Yinjie Jiang; Xun Chen; Mingrui Cheng; I-Chun Lin; Boliang Li; Xinjie Zhu; Guanghan Xu; Huamao Miao; Xiaoying Wang; Xingtao Zhou (BMC Ophthalmology)
Abstract Background To evaluate the biosafety, reduction in anterior capsule opacification, and fluctuation in intraocular pressure (IOP) of a new phakic refractive lens (PRL) with a sinusoidal drainage groove design. Methods This self-controlled experiment was performed on eight eyes of four rabbits. Each rabbit was implanted with a sinusoidal PRL (PRL-S5) in the right eye and a conventional posterior chamber PRL (PC-PRL) in the left eye. Slit-lamp examinations, optical coherence tomography, and IOP evaluation were performed before surgery and at 1 day, 1 week, 3 months, 6 months, and 1 year postoperatively in each eye. Gross examination, histopathology, and electron microscopy of the capsule and PRL were performed 1 year postoperatively. Results On slit-lamp examination, the inflammatory reactions recovered one week after surgery. The PC-PRL group developed anterior subcapsular cataracts at 3 months postoperatively and diffuse and dense opacification of the cortex at 1 year. PRL-S5 showed mild local opacification in the optical zone 6 months postoperatively, which did not progress significantly. At 1 year, PC-PRLs had greater opacification (27.37–72.17%) than PRL S5 (6.63–66.96%). Three months after surgery, one eye in the PC-PRL group had scleral staphyloma, one eye had corneal edema, and one eye experienced nasal hepatic prolapse into the anterior chamber. One eye in the PRL-S5 group had papillary membranes but recovered 6 months postoperatively. Histopathological examination revealed liquefaction and necrosis of the opacified area in the center of the subcapsular membrane in both groups. Numerous granular bodies and fibrous precipitates were observed in epithelial cells in the opaque area. Electron microscopy showed that epithelial cells proliferated on the surface of all anterior capsule membranes, with no significant differences between the two groups. The capsular PC-PRL group showed anterior cortical proliferation and fibrosis. An IOP elevation was noted on the first postoperative day (18.8 to 37.9 mmHg). However, both the PC-PRL and PRL-S5 groups exhibited relatively stable IOP levels 1 week, 3 months, 6 months, and 1 year postoperatively. Conclusions The new PRL exhibited robust long-term biocompatibility. The sinusoidal groove design facilitated the maintenance of IOP stability without necessitating iridectomy and effectively mitigated the onset and progression of cataracts.